Two new species of the subgenus Brachyphytodecta Bechyně, 1948 (Coleoptera, Chrysomelidae, Gonioctena) from Sichuan, Southwest China - Cho, Hee-Wook (Zootaxa, 2017)
Two new species, Gonioctena (Brachyphytodecta) davidi sp. nov. and G. (B.) kangdingensis sp. nov., are described from Sichuan, China. Both are easily distinguished from other species by the presence of many micro-denticles on apicolateral surface of aedeagus, which is a unique character in the genus Gonioctena Chevrolat, 1836. A distribution map, photographs and diagnostic characters with illustrations of each species are included.